Different configurations of the non-minimal tensegrity triplex - Rutkiewicz, Andrzej (Archives of Civil Engineering, 2026)
The paper presents analyses on stable prestressed configurations of the tensegrity triplex with a non-minimal number of members. The non-minimal triplex is generally understood in the literature as the minimal triplex with three additional cables. However, this research shows that many different configurations can be obtained during prestressing. The prestressing procedure is led by changing the lengths of selected groups of members, i.e., struts, horizontal cables, cross cables, or additional members, assuming symmetry. A different view on prestressing is presented, where typically understood tensegrity natural configuration is separated into a newly called geometrical configuration and natural lengths of attached members. The presented interpretation of prestressing has a clear physical meaning. The calculations are based on the elastic energy approach, which is used to write the nonlinear equations that are afterward solved numerically. Two examples of prestressing the non-minimal triplex are presented, for slender and stocky prisms dimensions. The results show that additional members usually understood in the literature as additional cables, can as well serve as struts, which leads to a new group of structures with tensegrity features.